IRRIGATION AND LIMING AS FACTORS OF MAIZE YIELD INCREASES IN EASTERN CROATIA - Monika MARKOVIĆ; Marko JOSIPOVIC; Jasna SOSTARIC; Domagoj RASTIJA (Trakya University Journal of Natural Sciences, 2015)
Maize is the main field crop on arable lands in Croatia. Climatic changes, particularly temperature regime and precipitation quantities and their distribution during growing season had often adverse effects on maize yield. Therefore, irrigation of maize crops in critical periods is useful considering the variations among annual yields caused by water stressed conditions. Acid soils are covering one-third of agricultural soils in Croatia (about 832.000 hectares) and correction of pH by liming is also an important factor for increase and stabilization of annual yield values. The aim of this study was to review irrigation and liming effects on maize yield in eastern Croatia. Eastern Croatia covers an area of 12.454 km2 or 22.0% of the State territory. This region is termed as the “granary of Croatia” because 75% of wheat and 50% of maize harvested areas of the country are located in this region. Maize yields in the long-term (since 2000) irrigation experiments carried on since 2000 on Agricultural Institute Osijek increased by 20% in years with average climate conditions, while under drought conditions of three growing seasons in 2007, 2011 and 2012, yield increases were 32%, 36%, and 47%, respectively. Soil improvement by liming with increasing rates of carbocalk (by-product of sugar factory containing about 43% CaO and about 6% of organic matter) up to 60 t ha-1 was also a useful management practice, because in two experiments maize yields increased up to 25% (4-year average). However, for satisfied yield increases for 16% in both experiments the lowest amount of carbocalk needed for application was 15 t ha-1.